Livelihood strategies of farm households and distributional consequences / Siti Badariah Saiful Nathan - Saiful Nathan, Siti Badariah (2013)
Income diversification is common among Malaysian rural households. The diversification is undertaken as a means of managing risk or coping with any negative shocks to agricultural production. This study is aimed at identifying the livelihood strategies of rural households in the Northwest Selangor Integrated Agricultural Development Area and determining the effect of non-farm income sources on income inequality. More than 71 percent of farm households are found to be involved in diversification with ex-ante risk management being the main motive for diversification. High and medium income households are more involved in high-return non-farm wage employment while low income households in low-return agricultural-wage employment. Through the use of cluster analysis, four livelihood clusters were identified: highly specialized in farming, farming and agricultural-wage employment, specialization in non-farm employment, and finally, farming and non-farm employment. Households in livelihood clusters that combine farming and non-farm employment have significantly higher monthly percapita income. The results from the multinomial logit regression of livelihood selection show that the size of cultivated land has a significant negative effect on the selection of a diversified livelihood strategy compared to farming dominated strategy. In selecting the most remunerative livelihood cluster, household size, the number of working members, and the average education of working members are significant determinants. This implies that higher education is a barrier to the selection of a livelihood cluster that specializes in non-farm employment. Other non-farm incomes and having borrowing experience are significant to the selection of livelihood clusters that combine farming and agricultural-wage employment or non-farm employment. The Gini coefficient for overall inequality is 0.400 but without non-farm income the Gini coefficient is lower with 0.382. This suggests that non-farm income is a source of increasing income inequality. Income is also more unequally distributed in livelihood clusters that combine farming with non-farm employment. The decomposition of overall inequality reveals that the largest contributor to overall inequality is farm income (59 percent) while non-farm income contributes only 36 percent. In the decomposition of overall inequality by household assets using the regression-based approach, human capital was found to be the largest contributor to overall inequality through its effect on the inequality of non-farm wage and non-farm self-employment incomes. In terms of specific household assets, the important contributors to inequality are the number of working members, the average education of working members, the proportion of land owned, the size of cultivated land, credit access, the value of farm equipment owned, and household location. The overall importance of non-farm activities suggests that the promotion of rural non-farm activities should be an important component of any rural development strategy in Malaysia. Nonetheless, policy makers must also consider the possibility for any intervention with the likelihood of creating barriers to entry that may limit the ability of low income households to take advantage of non-farm employment opportunities, especially the most remunerative and thus worsening inequality. The links between certain assets and activities imply that a particular policy is unlikely to fit different situations across households in different granary areas and that location specific policies are necessary.